Social identity and social integration: a meta-analysis exploring the relationship between social identity and social integration - Hu, Jieyi; Cheung, Chau Kiu Jacky (Frontiers in Psychology, 2024)
Social identity formation is crucial for psychosocial development, particularly in the case of migrating adults. A body of research exploring how social identity influences social integration among migrants shows that social identity affects social integration through a range of moderators and procedures. This study reports on a meta-analysis of 33 studies with 47 cases (total N = 33,777; Fisher’s z = 0.33, moderate effects) examining the relationship between social identity and social integration in research conducted from 2005–2020. The research findings suggest that social identity can affect social integration directly without any moderators, indicating that most of the identified moderators in the previous studies are sample-specific variables. More importantly, the effects of various aspects of identities exert similar degrees of impact (moderate effect) on social integration; in other words, the usefulness of analyzing different aspects of social identity on social integration is challenged.